ORCA Algorithm for Unit Commitment Considering Electric Vehicle Inclusion - A.N. Afandi (Journal FORTEI-JEERI, 2021)
The most cost-effective operation of a power system is achieved in practice by combining different types of producing units to create a committed power plan to satisfy load demand changes at all periods of operation. To reduce overall costs while upholding set limitations, power outputs from generating units are distributed based on load demand at a certain moment. Economic Dispatch models are used to account for changes in load demand to compute the overall cost variations of operation to fulfill a unit commitment (UC). Orca Algorithm is used in this work to solve the UC problem with the IEEE-62 bus system as the model, where loads are linked with flexible loads where the flexible load in this study is determined by the driving habits of an electric vehicle (EV). The simulation results show that the Orca Algorithm solves the problem in the fewest iterations possible. Computations used to compute load demand changes over all periods are fast and smooth, with high convergence. UC problem is carried out in various power outputs, and total operating expenses. Furthermore, the EV has different driving characteristics as well as power users to cover the entire route for driving patterns with one-way and two trips.